ANALISIS KERUSAKAN DAN PERAWATAN MESIN INVESTMEN CASTING MENGGUNAKAN METODE PREVENTIVE MAINTENANCE OPTIMIZATION (PMO) PADA DEPARTEMEN DIE CASTING PT. MITRAMETAL PERKASA - Indra Prasetia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Production machine reliability is a fundamental factor in maintaining operational continuity within the manufacturing industry. PT. Mitrametal Perkasa, specifically in the Die Casting Department, faces challenges due to the high rate of sudden breakdowns in investment casting machines. This condition results in significant downtime and increased operational costs because the current maintenance strategy remains largely reactive. This study aims to analyze machine failure patterns and determine optimal maintenance intervals using the Preventive Maintenance Optimization (PMO) method. Research data were sourced from the 2025 machine maintenance performance reports, analyzed using reliability parameters such as Mean Time To Failure (MTTF) and Mean Time To Repair (MTTR). The results indicate that determining maintenance intervals based on historical data through the PMO approach provides more accurate maintenance schedule recommendations compared to conventional schedules. The implementation of this strategy is expected to enhance machine availability, minimize sudden failures, and optimize long-term maintenance cost efficiency at PT. Mitrametal Perkasa.